Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1108/ijm-01-2012-0017
|View full text |Cite
|
Sign up to set email alerts
|

Glass ceiling or sticky floor? Quantile regression decomposition of the gender pay gap in China

Abstract: Purpose -The purpose of the paper is to analyse how the male-female pay gap in China varies across the pay distribution and to provide evidence on the factors that influence that gap. Design/methodology/approach -The authors use the Recentered Influence Function modification of quantile regressions to estimate how the male-female pay gap varies across the pay distribution. The authors also decompose the pay gaps at different quantiles of the pay distribution into differences in endowments of wage determining c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
(76 reference statements)
2
27
0
Order By: Relevance
“…Sticky floor explains systematic ways in which women are denied of opportunities to advance from lower elchlon position in their organizations and a large pay gap exists between each echelon of the wage distributions (Cotter et al, 2001). Arulampalam (2007) and Xiu and Gunderson (2014) also make an important argument by stating that the concentration of women in lower paying jobs result in depressed wages for women. Studies that investigate the above concepts argue that women are automatically excluded from opportunities for growth when they are systematically concentrated in lower echelon positions or when they are denied promotion opportunities that lead to management positions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sticky floor explains systematic ways in which women are denied of opportunities to advance from lower elchlon position in their organizations and a large pay gap exists between each echelon of the wage distributions (Cotter et al, 2001). Arulampalam (2007) and Xiu and Gunderson (2014) also make an important argument by stating that the concentration of women in lower paying jobs result in depressed wages for women. Studies that investigate the above concepts argue that women are automatically excluded from opportunities for growth when they are systematically concentrated in lower echelon positions or when they are denied promotion opportunities that lead to management positions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in this group particularly report that access to promotion at higher levels of organizational hierarchy was less persistent in the public sector than in the private and multi-sector contexts (Dolan, 2004; Lewis, 1986b; Peterson & Saporta, 2004; Powell & Butterfield, 1994). However, few studies conducted in the public sector and studies that compared public and private sectors showed evidence of sticky floors in the public sector indicating the lack of equal opportunity for women to advance in their organizations (Arulampalam, Alison, & Bryan, 2007; Miller, 2009; Peterson & Saporta, 2004; Xiu & Gunderson, 2014).…”
Section: Sector Comparison By Themementioning
confidence: 99%
“…The aim of this study is to examine the effect of entrepreneurship on women's earnings as well as the gender earnings gap among entrepreneurs in China. Existing studies find that women in China receive lower pay than men across various occupations (Xiu and Gunderson 2015) and throughout the income distribution (Chi and Li 2014; Xiu and Gunderson 2014). If there indeed exist both an entrepreneurial earnings gap and a gender earnings gap, how would the two interplay with each other?…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the values employers attach to wage determination have a strong bearing on gender pay gaps – particularly where these have limited connection with factors such as the skills and responsibilities of the work. This absence of detailed guidelines means this is often the case in China: survey evidence has identified considerable heterogeneity in approaches to pay determination, specifically in the ways that ‘different characteristics are rewarded’ (Xiu and Gunderson, 2014: 306). In the public sector, for example, morality, competence, effort and seniority are among the core norms traditionally used for pay determination, performance review and promotion (e.g.…”
Section: Wage-setting Arrangements: the Composition And Determinationmentioning
confidence: 99%